Answer :

devishri1977

Answer:

Step-by-step explanation:

y = x² + x - 4

When x = -3;   y = (-3)² + (-3) -4

                          = 9 - 3 - 4 = 9-7

                       y =  2

When x = -2;   y = (-2)² + (-2) -4

                          = 4 - 2 - 4 = 4 - 6

                          y =  -2

When x = 0;   y = 0 + 0 -4

                      y =  -4

When x = 1;   y = 1 + 1 - 4

                      =  2 - 4

                       y =  -2

When x = 3;   y = (3)² + 3 -4

                          = 9 + 3 - 4 = 12-4

                       y =  8

Other Questions